2-Oxiranyl-pyridines: Synthesis and Regioselective Epoxide Ring Openings with Chiral Amines as a Route to Chiral Ligands - Marzena Wosińska-Hrydczuk; Jacek Skarżewski (Heteroatom Chemistry)
New epoxides, derivatives of pyridine, 2,2′-bipyridine, and 1,10-phenanthroline, were synthesized from the respective α-methylazaarenes. The obtained racemic 2-oxiranyl-azaarenes along with styrene oxide and trans-stilbene oxide were submitted to the ring opening with chiral primary amines as a chiral auxiliary. The most effective reaction was run in the presence of Sc(OTf)3/diisopropylethylamine for 7 days at 80°C, affording a good yield of the amino alcohols. Except for styrene oxide which gave both α- and β-amino alcohols, the reactions led regioselectively to the corresponding diastereomeric β-amino alcohols. The resulting diastereomers were separated, and the configurations of their stereogenic centers were established. The obtained enantiomerically pure 2-pyridinyl- and 6-(2,2′-bipyridinyl)-β-amino alcohols were tentatively tested as chiral ligands in the zinc-catalyzed aldol reaction.